PENERAPAN MODEL PEMBELAJARAN MODIFIED FREE INQUIRY BERBASIS ECOPRENEURSHIP UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK PADA MATERI TEORI KINETIK GAS - NURIN NISA, AZKIA; HARIYONO, EKO (Inovasi Pendidikan Fisika, 2019)
This research aims to describe student?s learning response toward an Ecopreneurship-Based Modified Free Inquiry Model on physics learning especially Kinetic Gasses Theory matter. The type of research is True Experimental Design and Posttest Only Control Group Design. The participants of this research is student from an experimental class and control class with normally distributed. Data was collected from questionnaire. Data was analyzed using the response questionnaire score. The results show that an Ecopreneurship Based Modified Free Inquiry Learning Model on Kinetic Gasses Theory matter obtained student well response. Keywords: Ecopreneurship, Modified Free Inquiry, Kinetic Gasses Theory, Learning Responses